PERANCANGAN APLIKASI BELAJAR BERSAMA MENGGUNAKAN TEKNIK POMODORO BERBASIS WEB - Vieri Fernando; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2022)
The Pomodoro technique is a learning technique by means of time management. The advantage of using the pomodoro technique is that it can help train the brain to focus on what is being done, so that over time the brain is trained to focus on one thing so that when working on anything it can be done perfectly and quickly without being distracted. Sometimes when studying, students' minds are disturbed because they have multitasking habits, namely how to divide attention when working on different tasks simultaneously which results in only paying attention to certain parts of the whole that must be concentrated, resulting in the work not being completed, things like this happen because learning by learning techniques which is not correct.. The purpose of this research is to design a real-time interactive learning application where students can discuss directly with other participants. The application design uses the Multimedia Development Life Cycle method which consists of 6 stages, namely Concept, Design, Material Collecting, Assembly, Testing and Distribution. The design of this learning application uses the Pomodoro Technique to help students avoid things that distract them. The result of testing the application is that the application works well in the browser.